Mechanistic insight into mycobacterial MmpL protein function. Issue 5 (19th January 2016) - Székely, R.; Cole, S. T.
Summary: Mycobacterial cell walls are complex structures containing a broad range of unusual lipids, glycolipids and other polymers, some of which act as immunomodulators or virulence determinants. Better understanding of the enzymes involved in export processes would enlighten cell wall biogenesis. Bernut et al . (2015 ) present the findings of a structural and functional investigation of one of the most important transporter families, the MmpL proteins, members of the resistance‐nodulation‐cell division (RND) superfamily. A Tyr842His missense mutation in the mmpL4a gene was shown to be responsible for the smooth‐to‐rough morphotype change of the near untreatable opportunistic pathogen Mycobacterium bolletii due to its failure to export a glycopeptidolipid (GPL). This mutation was pleiotropic and markedly increased virulence in infection models. Tyr842 is well conserved in all actinobacterial MmpL proteins suggesting that it is functionally important and this was confirmed by several approaches including replacing the corresponding residue in MmpL3 of Mycobacterium tuberculosis . Structural modelling combined with experimental results showed Tyr842 to be a critical residue for mediating the proton motive force required for GPL export. This mechanistic insight applies to all MmpL proteins and probably to all RND transporters.